Sport for All Frail Bodies - Jespersen Ejgil (Sciendo, 2015)
Sport for All is a universal Olympic idea adopted by supranational institutions such as the Council of Europe, UNESCO, and the UN. Measures that need to be taken to ensure that all people have an equal opportunity to be included in sport are analyzed and discussed based upon a survey of sports and exercise participation in Denmark with a special focus upon people with impairments. The prevailing point of view is a special needs approach to sports participation, whether it is oriented towards separate or integrated forms of organization. It is often unclear whether this approach is aiming for equality of outcome, equality of chance or just a minimum threshold for sports and exercise activity. However, if we adopt a universal approach to Sport for all, then the focus is not on differences among people, but upon the commonalities among human beings in light of their diversity. This approach is associated with the understanding of "universal design" in the UN‟s Convention of the Rights of Persons with Disabilities and the WHO‟s International Classification of Functioning, Disability, and Health. In conclusion, it is highlighted that a more inclusive Sport for All movement is preferable to a segregated or integrated disability sport, provided the persons concerned have a say in every case.